Benign multiple sclerosis : aspects of neurodegeneration with soluble biomarkers and MRI imaging - Niiranen, Marja (Publications of the University of Eastern Finland, ISSN 1798-5706, 2024)
Benigni MS-tauti, näkökulmia neurodegeneraatioon liukoisten biomarkkereiden ja MRI-kuvantamisen keinoin.
Keywords: Biomarkers; Glial Fibrillary Acidic Protein; Intermediate Filaments; MS-tauti; multipelskleros; hyvänlaatuinen MS-tauti; ennustetekijä; aivoatrofia; neurofilamentti; benign multiple sclerosis; brain atrophy